The Effect of Self Concept and Learning Facilities On Students' Academic Achievement in Online Learning Moderated By Self Efficacy - Cahya, Septyan Budy; Veni Rafida; Raya Sulistyowati (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyze the influence of self-concept and learning facilities on the academic achievement of Business Education Study Program students in online learning moderated by self-efficacy. The variables studied are self-concept, learning facilities, and online learning self-efficacy. The urgency of this study is to explore various factors related to students' academic achievement in online learning to improve and help support the online learning process to be better, so that the expected learning objectives can be achieved. This type of research is survey research and has a quantitative approach. The population of this study was all students who were active and still taking online lectures, approximately 177 students. Meanwhile, the research sample was taken using the nonprobability sampling method with a saturated sampling technique. The data analysis technique used Moderated Regression Analysis (MRA). Based on the results of the study, self-concept and learning facilities have an influence on student achievement both partially and simultaneously. Furthermore, self-efficacy was found to moderate the influence of self-concept and learning facilities on student achievement.